Role of Efflux Pumps in Reduced Susceptibility to Tigecycline among Clinical Isolates of Acinetobacter baumannii - Mahapatra, Ashoka; Pati, Amresh; Gupta, Kavita (International journal of applied and basic medical research, 2022)
Abstract Background: Acinetobacter baumannii (A. baumannii) is a very well-known emerging pathogen and has become a major burden on healthcare system especially in intensive care units (ICUs). Tigecycline is the last resort drug for treatment of multidrug-resistant A. baumannii infections. However, non-susceptibility to this drug is a rising problem. Resistance to tigecycline is mediated by Resistance-nodulation-cell division (RND) efflux pumps. Objective: This study was done to detect efflux pump genes (adeABC) and regulator genes (adeS,adeR) responsible for tigecycline resistance among the clinical isolates of A. baumannii. Materials and Methods: A total of 150 OXA-51 confirmed clinical isolates were subjected for tigecycline susceptibility test by broth microdilution (BMD) method. All isolates irrespective of their MIC were subjected to conventional PCR for detection of efflux genes (adeABC) and regulator genes (adeRS). Results: Prevalence of tigecycline resistance was found to be 14 (9.33%) by the reference broth microdilution method (BMD). Overall prevalence of efflux genes was highest for adeB (69%) and lowest for adeR (29%). Combination of genes especially three, four or five were found more prevalent among resistant isolates with higher minimum inhibitory concentration (MIC). Conclusion: Combination of efflux genes confer higher MIC and can be a major contributor for resistance to tigecycline.